Identifying Entrepreneur Motivation which Influence to Business Performance in Start-Up Fashion Industry - Diana Putri, Sintia; Rahmatsyah Putranto, Nur Arief (Journal of Innovation, Business and Entrepreneurship, 2018)
Abstract. Many fashion industries have begun to decline and begin to disappear, but today the fashion industry has started to rise again because they have started to realize in terms of innovating. Innovation is meant not only from the product alone but from design to after sale. It is like something that has been we planned to aim the whole of process in develop a business. Fashion industry is the largest sub-sector in the creative economy, which is able to contribute 31% of income in this sector in 2017. The data’s prove that today everyone needs clothes to perform his daily activities. From these needs, the development of fashion industry began to grow and dominate the market. Therefore many people, especially among young people who opened a business in the field of fashion because the market is large and will always exist. This research are to find motivations of entrepreneur in fashion startup industry and to know the most influential entrepreneur motivation that affects to business performance with mix method analysis which are consist of qualitative and quantitative data. The interview is a qualitative data that the researcher use for to collect a material for develop a questionnaire. The questionnaire is quantitative data that the researcher use to spread the questionnaire to all of startup in fashion industry. The questionnaire has fulfilled by 95 respondent, using Microsoft Excel, SPSS, and processed through Logistic Regression. The findings founded that overall Entrepreneur motivation in Achievement of Startup Fashion industry affected the most The Business Performance. Economic, Achievement, and Social are variable that is influence entrepreneur in make a good performance in their business. While money or economic is significant for the growth for the business, but for the sustainability of company the Achievement aspect is more influential than that.Keywords: Achievement, Business Performance, Entrepreneur Motivation, Fashion industry, Startup